Rice (Oryza sativa L.) response on increased drought and salinity in the vegetative phase. Issue 1 (1st December 2022) - Ichsan, C N; Erida, G; Hayati, M; Yuliawati,
Abstract: Environmental stress is a global threat to provide the world's food. Drought and salinity are the main threats to agricultural land productivity. This is a challenge in implementing SDGs 2030 as well as an opportunity if we are able to use germplasm to overcome various environmental stresses. Research on 2 varieties of rice Inpari 42 agritan as a comparison variety and varieties Sigupai which is a local variety of Aceh originating from Abdya. This study used a 2x3x6 split plot design with 108 experimental units and 324 experimental pots. There is an interaction between varieties when salinity occurs and salinity level on the growth of rice plants in the vegetative phase and electrical conductivity in soil and water which shows different responses between the Inpari 42 Agritan variety and the Sigupai varieties. On the electrical conductivity of the Sigupai. variety, it was better able to reduce Ec at different levels of salinity and time of occurs in the vegetative phase. Meanwhile, Inpari 42 Agritan is more capable of increasing growth under conditions of increased salinity in the vegetative phase. The local variety Sigupai, the rate of growth reduction is also relatively low compared to that without salinity. This is an opportunity to deal with drought and salinity that can occur anytime and anywhere due to drought, water management and improper fertilization that can occur anywhere. It is a challenge to overcome drought and lowering salinity with the use of local varieties and appropriate agronomic practices.